Recent progress on anti-nociceptive effects of carbon monoxide releasing molecule-2 (CORM-2) - Khir, Nurul Ajilah Mohamed; Noh, Ain’ Sabreena Mohd; Long, Idris; Zakaria, Rahimah; Ismail, Che Aishah Nazariah (Molecular and cellular biochemistry, 2024)
The role of carbon monoxide (CO) has evolved albeit controversial disputes on its toxicity. This biological gasotransmitter participates in the endogenous regulation of neurotransmitters and neuropeptides released in the nervous system. Exogenous CO gas inhalation at a lower concentration has been the subject of investigations, which have revealed its biological homeostatic mechanisms and protective effects against many pathological conditions. This therapeutic procedure of CO is, however, limited due to its immediate release, which favours haemoglobin at a high affinity with the subsequent generation of toxic carboxyhaemoglobin in tissues. In order to address this problem, carbon monoxide releasing molecule-2 (CORM-2) or also known as tricarbonyldichlororuthenium II dimer is developed to liberate a controlled amount of CO in the biological systems. In this review, we examine several potential mechanisms exerted by this therapeutic compound to produce the anti-nociceptive effect that has been demonstrated in previous studies. This review could shed light on the role of CORM-2 to reduce pain, especially in cases of chronic and neuropathic pain.